1998
DOI: 10.1038/sj.onc.1201657
|View full text |Cite
|
Sign up to set email alerts
|

EGF receptor signaling inhibits keratinocyte apoptosis: evidence for mediation by Bcl-XL

Abstract: Signaling through the epidermal growth factor receptor (EGFR) has been primarily implicated in the growth of epithelial cells including keratinocytes. However, the mechanism by which EGFR stimulation promotes keratinocyte cell growth is poorly understood. Here we report that human keratinocytes undergo apoptosis when incubated with the blocking EGFR monoclonal antibody 225 IgG, or PD153035, a highly speci®c EGFR tyrosine kinase inhibitor. Endogenous mRNA and protein levels of Bcl-X L , a member the Bcl-2 famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 37 publications
7
68
1
1
Order By: Relevance
“…The exact mechanism of the regulation of Bcl-x expression is still unknown. It has been shown that the reduction in apoptosis of keratinocytes induced by EGF activation is mediated by Bcl-xl (Stoll et al, 1998). In this study, ERK activation was not examined.…”
Section: Discussionmentioning
confidence: 86%
“…The exact mechanism of the regulation of Bcl-x expression is still unknown. It has been shown that the reduction in apoptosis of keratinocytes induced by EGF activation is mediated by Bcl-xl (Stoll et al, 1998). In this study, ERK activation was not examined.…”
Section: Discussionmentioning
confidence: 86%
“…In support of this hypothesis, recent studies have suggested that Bcl-x L may play a role in protecting keratinocytes from death signals induced by cell adhesion receptors and the EGF-R (Rodeck et al, 1997;Stoll et al, 1998). In addition, skin from transgenic mice that overexpress Bcl-x L has been shown to be much more resistant to UV radiation (Pena et al, 1997), suggesting that Bcl-x L may be important in keratinocytes to survive UVinduced damage.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have demonstrated the importance of cell adhesion and the activation of the epidermal growth factor receptor (EGF-R) to keratinocyte cell survival (Rodeck et al, 1997;Stoll et al, 1998). In these studies, the inhibition of cell adhesion or the blocking of EGF-R activation caused keratinocytes to become more susceptible to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…3D). Bcl-2 family proteins inhibit apoptosis induced by variety of stimuli, including Fasmediated apoptosis (37)(38)(39). We assessed the expression of the antiapoptotic protein Bcl-xL by Western blotting 10 h after the injection of anti-Fas antibody.…”
Section: Expression Of Egf-r Ligands In Mouse Liver After the Adminismentioning
confidence: 99%